Investigation of genetic polymorphism of Russian rape and turnip rape varieties using SSR and SRAP markers - I. A. Klimenko; V. T. Volovik; A. A. Antonov; V. A. Dushkin; A. O. Shamustakimova; Yu. M. Mavlyutov (Вавиловский журнал генетики и селекции)
Rapeseed (Brassica napus L.) and turnip rape (B. rapa L. subsp. campestris (L.)) are important agricultural plants widely used for food, fodder and technical purposes and as green manure. Over the past decades, a large number of perspective varieties that are being currently cultivated in every region of Russia have been developed. To increase the breeding efficiency and facilitate the seed production, modern molecular-genetic techniques should be introduced as means to estimate species and varietal diversity. The objective of the presented research study was to investigate DNA polymorphism of the rapeseed and turnip rape varieties developed at Federal Williams Research Center of Forage Production and Agroecology and detect informative markers for varietal identification and genetic certification. To genotype 18 gDNA samples, 42 and 25 combinations of respective SSR and SRAP primers were used. The results obtained demonstrate that SRAP markers were more effective for polymorphism analysis: 36 % of the tested markers revealed genetic polymorphism compared with only 16.7 % of microsatellite loci. Molecular markers to detect differences at interspecific and intervarietal levels have also been found. For the investigated set, such microsatellite loci as Na12A02, Ni2C12, Ni02-D08a, Ra02-E01, Ni03H07а and SRAP-marker combinations as F13-R9, Me4-R7, F11-Em2, F10-R7, F9-Em2 and F9-R8 proved to be informative. Application of the two marker techniques made it possible to detect a higher level of DNA polymorphism in plants of different types (spring and winter varieties) if compared against the intervarietal differences within a species or a group. According to Nei’s genetic diversity index, in the cluster of winter rapeseed, VIK 2 and Gorizont varieties had the longest genetic distance, and in the spring cluster, these were Novosel and Veles. A high level of similarity was found between Vikros and Bizon winter rapeseed varieties. The results obtained have a high practical value for varietal specification of seed material and genetic certification of rapeseed and turnip rape varieties.